Phenomena related to autobiographical memory during initial consultations in couple psychotherapy - Zalewski, Bartosz (Przegląd Psychologiczny, 2022)
Objective The aim of this article is to seek the possibility of applying the conclusions of current research on the functioning of autobiographical memory to diagnostic practice in couple psychotherapy. The nature of memory processes determines the type of data that diagnosticians obtain from couples during consultation. Another aim is to support the development of methodological competencies of psychologists-diagnosticians working with couples, by providing knowledge about the operation of memory mechanisms during initial consultation meetings. Theses Research on autobiographical memory shows that the content of memories significantly depends on the purpose, context, and audience for which it is recalled. A thesis explored in this article is that in the specific context of the consultations for couple psychotherapy, memories are recalled by partners under the influence of strong emotions, and in order to talk about the couple’s problems partners often protect each person against negative evaluations by therapists. At the same time partners try to introduce and maintain elements of relational identity of each partner. Conclusions Autobiographical memory is a valuable source of information about the couple’s past. Knowledge about memory mechanisms allows therapists to adequately assess the quality of collected data and then formulate appropriate diagnostic hypotheses. At the same time, consulting sessions are specific environments for recalling memories. For proper assessment, it is necessary to analyze both the content of memories and the way they were introduced into consultation. Collecting important information about the mental life of each partner is also possible thanks to a good diagnostic alliance.